Digital Signature Authentication for Android Smart Phones (International Journal of Engineering and Computer Science, 2014)
Due to the innovations in Mobile technologies, Gestures play an important role for the Authentication in the mobile devices. With increasing popularity of the Authentications, the security risks are also growing and that is evident in the incidents of UnAuthentication in terms of various kinds. Therefore it is essential to have a mobile based Authentication system for security. Gestures allow users to interact with your app by manipulating the screen objects you provide. Security systems are rapidly being developed, as well as solutions such as remote control systems. However, even with these solutions, major problems could still result after a mobile device is lost. In this thesis, we present our upgraded Lock Screen system, which is able to support authentication for the user’s convenience and provide a good security system for smartphones. We also suggest an upgraded authentication system for Android smartphones.